Arterial stiffness, renal function and renal blood flow in patients with coronary artery disease, arterial hypertension and type 2 diabetes mellitus - Elena Vasilievna Oskola; Anna Timofeevna Shubina; Alsu Rafhatovna Zairova; Marina Vladimirovna Andreevskaya; Roksana Mirabovna Bogieva; Olga Alexandrovna Pogorelova; Marina Grigorievna Bolotina; Tatiana Valentinovna Balahonova; Anatoliy Nikolaevich Rogoza; Yury Alexandrovich Karpov (Сахарный диабет)
Aim. To investigate the relationship between changes in indicators of arterial stiffness of various types of vessels, hemodynamic pulsatility, renal function and renal blood flow in patients with coronary artery disease (CAD) and arterial hypertension in the presence or absence of type 2 diabetes mellitus (T2DM). Materials and Methods. The study included 96 patients with CAD and arterial hypertension; among them, 54 subjects had T2DM and 42 did not. Сarbohydrate and lipid metabolism, renal function, stiffness of various types of arteries, parameters of hemodynamic pulsatility and renal blood flow were investigated. Results. Arterial stiffness of various types of vessels was increased in the T2DM group: carotid?femoral pulse wave velocity as a marker of aortic stiffness (a vessel of the elastic type) was increased by 16% (p